Analysis of Batik Industry Wastewater Quality Treated with Activated Charcoal from Coconut Fronds - Sulistiyaningtyas, Ayu Rahmawati; Nesa Fitriani Fahria (Indonesian Journal of Environment and Sustainability Issues, 2024)
The increasing growth and development of population is directly proportional to the increase in activities carried out by humans. Human clothing and lifestyle needs have increased very rapidly which has had an impact on the development of the textile industry, one of which is the batik industry. Many fans of batik production produce waste water which can pollute the waters around residents. This can have a detrimental impact on the environment because there are organic compounds that can cause environmental pollution. The coconut fronds that are often found are not used optimally. Therefore, researchers used coconut fronds made into charcoal as an adsorbent material for processing batik liquid waste. The research will be carried out for 1 month, from June to July 2023. Analysis of the quality of liquid waste will be carried out at the Baristan Laboratory. This type of research is experimental research. The research design uses 25 ml of batik waste treated with 3 grams of activated charcoal, 3.5 grams. , and 4 grams for 40 minutes. Data analysis uses the Effectiveness Formula. Data shows that activated charcoal is effective in reducing oil and fat in batik liquid waste. The higher the weight of activated charcoal for filtration, the higher the reduction in oil and fat levels. However, this does not apply to the COD and pH parameters. Activated charcoal can reduce COD levels with an average effectiveness of 20.32% mg/L, pH with an average of 12% and fatty oils with an average of 66% mg/L.